Continuidade de atratores para a discretização de problemas parabólicos usando o método de elementos finitos - Figueroa López, Rodiak Nicolai [UNESP] (2013)
In this work we study the approximation of semilinear parabolic di erential equations through their discretization via the nite element method. We prove that the attractors of discretization behave continuously when the step size tends to zero extending the results of [17]. We also calculate the rate of convergence of attractors in terms of step of discretization